Parametric Evaluation of Building Height Effects on Seismic Code Compliance of RC Special Moment Frames Using OpenSeesPy - Usman Wijaya; Romain Turpin; Liana Herlina; Jean Castaing-Lasvignottes; Dimas Prasasti Renandhito (Universitas Islam Raden Rahmat, Malang, 2026)
This study presents a parametric evaluation of building-height effects on the global seismic response and initial code-compliance indicators of reinforced concrete Special Moment Frames (RC-SMFs). The work is limited to linear response-spectrum analysis and global screening checks; nonlinear static analysis, non liner time-history analysis, and detailed SNI 2847 member design are outside the present scope. Three OpenSeesPy-based three dimensional models with 6, 9, and 12 stories were developed using the same structural plan, maximum analytical beam span of 9.5 m, Jakarta soft-soil seismic demand, and SNI 1726:2019 design parameters. The novelty of the study is an integrated OpenSeesPy parametric workflow that evaluates modal regularity, modal participating mass ratio, base-shear scaling, design drift, torsional response, and P-Delta stability in one SNI-oriented assessment process. The results show a regular modal sequence for all models, with Mode 1 and Mode 2 dominated by X- and Y- translation and, Mode 3 governed by torsion. As the number of stories increases, the fundamental period increases from 0.365 s to 0.537 s and 0.689 s, while the equivalent lateral force base shear increases from 7,918.73 kN to 11,878.09 kN and 15,837.45 kN. The maximum design drift increases with building height but remains far below the 2.0% allowable limit, while torsion ratios and P-Delta coefficients remain low. Thus, the adopted RC-SMF configuration satisfies the selected linear global screening checks, although final acceptance still requires nonlinear assessment and detailed member design.